Simple and basic yet vital and essential health services: an exploration of perception of junior health care service providers regarding rural health services in India - Joshi, Sudhir Chandra; Joshi, Rita (International Journal Of Community Medicine And Public Health, 2018)
Background: Health services should be scientifically reviewed and researched continuously.. In 2017, at the occasion of completion of seven decades of the India's Independence, a self-funded “doctors' perception study project” was launched. Present paper is an outcome of this project which will soon be followed by similar projects involving other stakeholders of health care as well. Methods: Fifteen individual face to face in depth interviews (FFIDIs) and ten focus group discussions (FGDs) were conducted during the year 2017 among the junior level health care providers working at a rural health training center. Thematic (content) analysis method was used. Results: A big gap exists between the concept and its implementation. Several ‘people factors’ and ‘system factors’ emerged besides quite a few ‘contradictions’, ‘malpractices’ and ‘deficiencies’. Perceptions regarding various ‘priority domains’ for improvement, ‘needs’ and ‘strategies’ were also explored. The emphasis was on improving peoples’ awareness action and access; staff recruitment, health care facilities and patient referral. Conclusions: Access barriers are disastrous and devastating for the poor and the disabled. There is a close mutual relation among the various issues. Chaos is being allowed to exist in which there are irrational use of drugs, mushrooming of ‘quacks’ and diversion of resources from public to private sector. Addressing all the issues requires peoples’ awareness and action along with political and administrative vision and will. A different politics is needed. Introspection, internal reforms and more community engagement is expected from the medical community.